Nickel oxide nanoparticles thin film saturable absorber for 1-micron pulsed all-fibre lasers operation - Al-Masoodi, Ahmed Hasan Hamood; Ahmed, Mahmoud Hazzaa M.; Latiff, Anas Abdul; Arof, Hamzah; Harun, Sulaiman Wadi (Taylor & Francis, 2018)
A passive Q-switched and mode-locked ytterbium-doped fibre laser (YDFL) pulse generation using a nickel oxide thin film as a saturable absorber is reported. The nickel oxide nanoparticle thin film was fabricated by a simple processing technique, and it has a modulation depth of 39% and saturation intensity of 0.04 MW/cm 2 . The saturable absorber was constructed by inserting a small piece of the film between two fibre ferrules. Then it was integrated in a YDFL cavity. The Q-switching operation started at a threshold pump power of 117.73 mW with an initial wavelength of 1073.5 nm. When the pump power was raised from 117.73 to 133 mW, the repetition rate grew from 9.5 to 15.8 kHz. The pulses had a maximum pulse energy of 478 nJ. Furthermore, a stable self-started mode-locked pulse was also succesfully generated at the threshold pump power of 97.3 mW. The central wavelength and repetition rate of the laser were 1037.72 nm and 23 MHz, respectively. The maximum pulse energy of 0.56 nJ and a peak power of 26.4 W were recorded at a pump power of 137.5 mW.